Lateral gene transfer of p-cresol- and indole-producing enzymes from environmental bacteria to Mastigamoeba balamuthi - Nývltová, Eva; Šut'ák, Robert; Žárský, Vojtěch; Harant, Karel; Hrdý, Ivan; Tachezy, Jan (Environmental microbiology, 2017)
p-Cresol and indole are volatile biologically active products of the bacterial degradation of tyrosine and tryptophan respectively. They are typically produced by bacteria in animal intestines, soil and various sediments. Here, we demonstrate that the free-living eukaryote Mastigamoeba balamuthi and its pathogenic relative Entamoeba histolytica produce significant amounts of indole via tryptophanase activity. Unexpectedly, M. balamuthi also produces p-cresol in concentrations that are bacteriostatic to non-p-cresol-producing bacteria. The ability of M. balamuthi to produce p-cresol, which has not previously been observed in any eukaryotic microbe, was gained due to the lateral acquisition of a bacterial gene for 4-hydroxyphenylacetate decarboxylase (HPAD). In bacteria, the genes for HPAD and the S-adenosylmethionine-dependent activating enzyme (AE) are present in a common operon. In M. balamuthi, HPAD displays a unique fusion with the AE that suggests the operon-mediated transfer of genes from a bacterial donor. We also clarified that the tyrosine-to-4-hydroxyphenylacetate conversion proceeds via the Ehrlich pathway. The acquisition of the bacterial HPAD gene may provide M. balamuthi a competitive advantage over other microflora in its native habitat.
Keywords: S-adenosylmethionin; operon; Gene Transfer, Horizontal; Cresols; Operon; Bacteria; Animals; karboxylyasy; Genes, Bacterial; Archamoebae; Carboxy-Lyases; kresoly; S-Adenosylmethionine; přenos genů horizontální; Indoles; zvířata; bakteriální geny; indoly